NADPH oxidase 4 inhibition is a complementary therapeutic strategy for spinal muscular atrophy - El Khoury, Mirella; Biondi, Olivier; Bruneteau, Gaelle; Sapaly, Delphine; Bendris, Sabrina; Bezier, Cynthia; Clerc, Zoé; Akar, Elias Abi; Weill, Laure; Eid, Assaad A.; Charbonnier, Frédéric (Frontiers in Cellular Neuroscience, 2023)
Spinal muscular atrophy (SMA) is a fatal neurodegenerative disorder with childhood-onset, characterized by motor neuron (MN) degeneration that induces severe muscular atrophy. SMA is caused by insufficient Survival of Motor Neuron (SMN) protein expression. Therapies aimed at increasing SMN in patients have proven their efficiency in alleviating SMA symptoms but not for all patients and with limitations. Thus, combinational therapies are warranted. Here, we reported that oxidative stress is an early event in the spinal cord of severe type SMA-like mice, and we identified NADPH oxidase 4 (NOX4), as a source of this stress. Inhibition of NOX4 by GKT137831/Setanaxib, a drug presently in clinical development, by intrathecal injection significantly protected spinal MN from SMA-induced degeneration and led to the relative maintenance of neuromuscular junction integrity. These cellular improvements were associated with a significant increase in lifespan and motor behavior of the mice. At the molecular level, GKT137831 activated the pro-survival AKT/CREB signaling pathway, leading to a significant increase in SMN expression in SMA MNs. Most importantly, we found that the per os administration of GKT137831 acted synergistically with a FDA-validated SMN-upregulating treatment suggesting that GKT137831 may constitute a complementary therapeutic strategy to fight against SMA.